Extending the vase life of Gerbera (Gerbera hybrida) cut flowers using chemical preservative solutions - W.A.N.T. De Silva; J. P. Kirthisinghe; L.M.H.R. Alwis (Tropical Agricultural Research, 2015)
The experiment was conducted to find out a chemical preservative solution to extend the vase life and reduce the stem bending of gerbera (Gerbera hybrida). Calcium chloride (CaCl2; 1 %), lime juice (0.5 %), vinegar (0.6 %) and sucrose (2 %) were used in the eight treatments, arranged in a Complete Randomized Design with 10 replicates. The vase life and stem bending percentage were observed daily. Fresh weight of flower heads and stems were measured. Flower quality was recorded after 12 days by a scale developed for the said purpose. Qualitative data were analyzed by Kruskal-Wallis test and quantitative data were analyzed by using one way ANOVA. Significant differences (p<0.05) were observed in the fresh weight of flower heads and stems. The highest fresh weight of flower heads (7.3 g), fresh weight of stems (4.2 g), zero stem bending percentage and the maximum vase life (16 day) were obtained in the treatment containing sucrose 2 % + vinegar 0.6 % + CaCl2 1 % in distilled water. Tropical Agricultural Research Vol. 24 (4): 375-379 (2013)